2010
DOI: 10.1080/02640414.2010.502946
|View full text |Cite
|
Sign up to set email alerts
|

Systematically increasing contextual interference is beneficial for learning sport skills

Abstract: To better understand the contextual interference effect, in two experiments we investigated a form of practice schedule that provided novices with systematic increases in contextual interference. This new type of practice schedule was compared with traditional blocked and random scheduling for two types of sports skills. In Experiment 1, we tested the hypothesis that practising variations of the same task with systematic increases in contextual interference would lead to superior performance compared with bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
118
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 18 publications
12
118
0
8
Order By: Relevance
“…Specifically, Goodwin and Meeuwsen (1996) found that during the transfer test, the random and block-random groups performed significantly better than the block group at the longer 6.23-m distance. Similarly, Porter and Magill (2010) found that the combination (Increasing) group performed significantly better than the block and random groups in retention testing and significantly better than the random group in transfer testing. Guadagnoli et al (1999) reported a significant interaction between skill and type of practice, whereby novice golfers significantly improved their putting accuracy more through block practice, whereas experienced golfers improved significantly more through random practice.…”
Section: Block Versus Random Practicementioning
confidence: 98%
See 4 more Smart Citations
“…Specifically, Goodwin and Meeuwsen (1996) found that during the transfer test, the random and block-random groups performed significantly better than the block group at the longer 6.23-m distance. Similarly, Porter and Magill (2010) found that the combination (Increasing) group performed significantly better than the block and random groups in retention testing and significantly better than the random group in transfer testing. Guadagnoli et al (1999) reported a significant interaction between skill and type of practice, whereby novice golfers significantly improved their putting accuracy more through block practice, whereas experienced golfers improved significantly more through random practice.…”
Section: Block Versus Random Practicementioning
confidence: 98%
“…The three studies involving block and random practice differed in the number of acquisition days (1-4), but all involved novice golfers performing putting tasks over three distances, with a retention and/or transfer test a day after acquisition. In general, Goodwin and Meeuwsen (1996) and Porter and Magill (2010) reported no significant difference in putting error between the block and random groups in the retention and transfer tests across all three assessed distances. There were however some exceptions to this generalisation.…”
Section: Block Versus Random Practicementioning
confidence: 98%
See 3 more Smart Citations